LIFE PERSPECTIVE OF PEOPLE WHO ARE IN THE CONDITIONS OF ANTI-TERRORIST OPERATION (ATO) - Pavlenko, Oksana (PSYCHOLOGICAL JOURNAL, 2019)
The article deals with the peculiarities of the formation of the life perspective of people who are in the conditions of ATO. The main parameters, functions and forms of awareness of personal life perspectives are revealed. The following characteristics and components of the life perspective of the individual are singled out: differentiation / non-differentiation - the content component, optimism / pessimism - the emotional and experiencing component, realism / unrealism - the pragmatic-practical component, normativity / personality - the semantic component. According to these components, the author made the analysis of the structure of the life perspective of the respondents in the ATO zone, in particular ATO fighters, internally displaced people, residents of the "gray" zones and residents of stable territories of Ukraine. The divergences in the presented perspectives of their own lives in the consciousness of these groups of respondents were revealed and analyzed. It was stated that the least differentiated perspective is among the representatives of the military men participating in the ATO. Optimism about their own future was demonstrated by all categories of respondents. The sense of the own perspective is at a fairly high level for all groups of respondents related to ATO, but events are most often selected on a normative basis, as opposed to representatives of the group of stable territories. The reflexivity concerning the actions which are to be taken in order to reach this or that planned or anticipated event was shown by the representatives of IDP group, they surpassed the representatives of the group of stable regions for this indicator. According to the results of the conducted research, we can note that for the construction of a differentiated, optimistic, realistic and personal perspective of the individual, it is necessary to take into account the content of the perspective, its emotional assessment, semantic and pragmatic-practical component. The results of the above research can be used to create a program of psychological assistance to ATO fighters, IDP and residents of the border areas with the zone of ATO (gray zones) to facilitate the construction of their own future perspectives.